2016
DOI: 10.1152/ajpendo.00503.2015
|View full text |Cite
|
Sign up to set email alerts
|

Formoterol decreases muscle wasting as well as inflammation in the rat model of rheumatoid arthritis

Abstract: Adjuvant-induced arthritis is an experimental model of rheumatoid arthritis that is associated with body weight loss and muscle wasting. β2-adrenergic receptor agonists are powerful anabolic agents that trigger skeletal muscle hypertrophy and have been proposed as a promising treatment for muscle wasting in human patients. The aim of this work was to determine whether formoterol, a selective β2-adrenoreceptor agonist, is able to ameliorate muscle wasting in arthritic rats. Arthritis was induced in male Wistar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 65 publications
(84 reference statements)
3
28
0
1
Order By: Relevance
“…have shown that treatment with a high dose of FOR (2000 μg kg −1 ) up‐regulated the protein content of LC3‐I and LC3‐II and the mRNA levels of Map1lc3b but did not change the protein content of autophagy protein markers like p62, concluding that ALS was unaffected by β 2 ‐agonist. Conversely, treatment with a low dose of FOR (50 μg kg −1 ) reduced LC3 lipidation in atrophic muscles from arthritic rats . Therefore, the FOR effects on ALS seem to vary accordingly to the doses.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…have shown that treatment with a high dose of FOR (2000 μg kg −1 ) up‐regulated the protein content of LC3‐I and LC3‐II and the mRNA levels of Map1lc3b but did not change the protein content of autophagy protein markers like p62, concluding that ALS was unaffected by β 2 ‐agonist. Conversely, treatment with a low dose of FOR (50 μg kg −1 ) reduced LC3 lipidation in atrophic muscles from arthritic rats . Therefore, the FOR effects on ALS seem to vary accordingly to the doses.…”
Section: Discussionmentioning
confidence: 95%
“…β 2 ‐agonists have been suggested to act at this level by increasing Akt/FoxO3 phosphorylation in fed and fasted states. As a consequence, the expression of some FoxO target genes, such as the muscle‐specific Ub‐ligases Atrogin‐1 and Murf1 , is down‐regulated by β 2 ‐agonists especially in atrophic muscles . Recently, two novel Ub‐ligases, Smart and Musa1 , controlled by FoxO have been identified as the critical genes for muscle loss; however, no information is available about their regulation by adrenergic system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained results 40 days post‐AIA induction showed firstly a reduced body mass in the AIA animals studied, which corroborates previous reports (Gómez‐SanMiguel et al ., ; Alabarse et al ., ). AIA‐induced body mass reduction is due mainly to sarcopenia, a phenomenon also observed in the rheumatoid cachexia.…”
Section: Discussionmentioning
confidence: 97%